2005
DOI: 10.1089/dia.2005.7.478
|View full text |Cite
|
Sign up to set email alerts
|

IRIS II Study: Intact Proinsulin Is Confirmed as a Highly Specific Indicator for Insulin Resistance in a Large Cross-Sectional Study Design

Abstract: Type 2 patients with elevated fasting intact proinsulin values can be regarded as being insulin resistant. The results confirm that fasting intact proinsulin is a suitable measure for beta-cell dysfunction and insulin resistance in type 2 diabetes and may be used to support therapeutic decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 42 publications
2
28
0
3
Order By: Relevance
“…A positive relationship between intact proinsulin levels and IR has been suggested in some, but not all, previous studies (6,7,40). Consistent with this, the absolute concentrations of both total and intact proinsulin were positively associated with the HOMA index of IR and negatively related to the Matsuda index of insulin sensitivity.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A positive relationship between intact proinsulin levels and IR has been suggested in some, but not all, previous studies (6,7,40). Consistent with this, the absolute concentrations of both total and intact proinsulin were positively associated with the HOMA index of IR and negatively related to the Matsuda index of insulin sensitivity.…”
Section: Discussionsupporting
confidence: 81%
“…While in healthy, non-diabetic subjects, these precursors constitute only a minor fraction of the total amount of secreted insulin, the release of proinsulin is significantly increased in patients with type 2 diabetes as well as in individuals with impaired glucose tolerance (IGT) (2)(3)(4)(5). A couple of recent studies have also reported an increase in intact proinsulin levels in insulin-resistant individuals (6,7), although this finding has not been confirmed by others (8,9). Nevertheless, the determination of intact proinsulin as a marker for the diagnosis of insulin resistance (IR) has been widely advocated (10).…”
Section: Introductionmentioning
confidence: 99%
“…An unfolded protein response could be initiated if such demand exceeds capacity, potentially leading to cell apoptosis (Pfützner et al 2004, Prentki & Nolan 2006. Elevated circulating proinsulin is an indicator for risk of developing diabetes in humans (Wareham et al 1999, Pfützner et al 2005, Prentki & Nolan 2006, Strawbridge et al 2011, von Berghes et al 2011. Proinsulin mutation in Akita mice results in accumulation of misfolded proinsulin that activates ER stressinduced βcell death (Hong et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The cross-sectional IRIS study was initially performed to identify diagnostic parameters for insulin resistance in non-insulin-treated patients with type 2 diabetes that are suitable for daily practice (13)(14)(15). Analysis of the same patient population presented here was performed to evaluate the correlation between cardiovascular risk, as identified by hsCRP risk assessment and b-cell dysfunction, and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of insulin resistance was performed by analysis of fasting intact proinsulin values or homeostatic model assessment (HOMA IR ) score calculation. Patients with intact proinsulin values exceeding the normal reference value of 11 pmol/L were considered to be insulin-resistant (14,15). In the case of normal intact proinsulin values, HOMA IR score calculation was applied, as previously published (17).…”
Section: Methodsmentioning
confidence: 99%